Morphometric Study of the Horizontal and Diagonal Length of the Human Mandible (Community Based Medical Journal, 2025)
The body of the human mandible has upper and lower borders. The lower border is smooth and called the base of mandible. The ramus has four borders, among them the inferior border is continuous with the base and ends with posterior border of ramus making the angle of the mandible. The cross-sectional, descriptive study was conducted in the Department of Anatomy, Mymensingh Medical College, Bangladesh, between July 2019 to June 2020, to determine the horizontal length and diagonal length of the human mandible. This study was done on 150 fully ossified dry mandibles. A non-random purposive sampling technique was adopted. The diagonal length was measured at the base of mandible from a point on symphysis menti to the posterior most point at mandibular angle, while the horizontal length was measured from the anterior margin of chin to a center point on a projected straight line along the posterior border of two mandibular angle. The mean (±SD) horizontal length of mandible was found 70.87 (±6.2) mm. The mean (±SD) diagonal length of at the right side of the mandible was found 81.90 (±5.3) mm and on the left side, it was 79.72 (±5.1) mm. This study will help the dental and maxillofacial surgeons in their field of practice. Forensic anthropology and prosthesis manufacturer will also be benefited from the study.  CBMJ 2025 January: Vol. 14 No. 01 P:118-121